2016
DOI: 10.1590/0102-6720201600040003
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factors and Cox2 in Wound Healing: An Experimental Study With Ehrlich Tumors

Abstract: Background: Healing is an innate biological phenomenon, and carcinogenesis acquired, but with common humoral and cellular elements. Carcinogenesis interferes negatively in healing. Aim: To evaluate the histological changes in laparotomy scars of healthy Balb/c mice and with an Ehrlich tumor in its various forms of presentation. Methods: Fifty-four mice were divided into three groups of 18 animals. First group was the control; the second had Ehrlich tumor with ascites; and the third had the subcutaneous form of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
1
8
0
1
Order By: Relevance
“…Immunohistochemical labeling revealed that administered dose was sufficient to significantly inhibit the production of COX-2. By image analysis, we found that the immunolabeling was prevalent in the parenchyma of the tumor, confirming that the main source of COX-2 was from the tumor cells (Salgado et al, 2016).…”
Section: Discussionsupporting
confidence: 56%
“…Immunohistochemical labeling revealed that administered dose was sufficient to significantly inhibit the production of COX-2. By image analysis, we found that the immunolabeling was prevalent in the parenchyma of the tumor, confirming that the main source of COX-2 was from the tumor cells (Salgado et al, 2016).…”
Section: Discussionsupporting
confidence: 56%
“…Improvement of neovascularization via angiogenesis is essential for the proper reepithelialization process by ensuring adequate nutrient supply, immune cells and oxygen. Rapid and robust vascular growth creates a vascular bed with more capillaries than the normal tissue 4,5,18,21,24 .…”
Section: Discussionmentioning
confidence: 99%
“…The main objective of this process is the restoration of tissue integrity and the maintenance of homeostasis. The healing process involves three sequential phases, which might be subdivided in four or five phases, that are dynamically related and not individualized: inflammatory phase, cellular proliferation phase, conjunctive tissue formation phase, contraction phase and the final wound remodelling phase 2,21,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Wound healing is a highly dynamic process involving a complex sequence of cellular and biochemical events, ranging from an immediate response to skin cell damage and invasive microbial signals to inflammatory, angiogenic, and ultimately fibroplasia and scar formation 3 , 4 , 21 , 28 . The phenomena occur simultaneously, self-regulated and interfering with each other.…”
Section: Discussionmentioning
confidence: 99%